2013
DOI: 10.1002/ente.201300052
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Gas‐Product‐Release Characteristics from Coal Pyrolysis and Hydrogasification

Abstract: Coal pyrolysis and hydrogasification were investigated in a laboratory‐scale pressurized fixed‐bed reactor to examine the effects of temperature, pressure, and catalyst on the gas productivity and yields under different gas atmospheres. The experimental results show that the methane yield is significantly higher under a hydrogen atmosphere. The release rate curve of methane during hydrogasification has three obvious peaks which are the results of coal devolatilization and rapid hydrogenation, the secondary rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Thus, the depolymerization/defragmenting of the H-bonding network exhibited priority responses via temperature-induced weakening/cleavage and dihydroxylation/dehydrogenation/demethylenation reactions. 76,77 This result was consistent with the high sensitivity of hydroxyl/ hydrocarbon groups in biomass-derived char to temperature changes. 31,32 As temperature increased, the subsequent reactions of residual fragments could result in more condensed structures, such as ether oxygen bonds and conjugated ketones.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the depolymerization/defragmenting of the H-bonding network exhibited priority responses via temperature-induced weakening/cleavage and dihydroxylation/dehydrogenation/demethylenation reactions. 76,77 This result was consistent with the high sensitivity of hydroxyl/ hydrocarbon groups in biomass-derived char to temperature changes. 31,32 As temperature increased, the subsequent reactions of residual fragments could result in more condensed structures, such as ether oxygen bonds and conjugated ketones.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…These complicated temperature responses for SBC-RFGs reflected more variability in structure, configuration, and composition caused by oxidation reactions. 77 Synergistic Evolved Relationships between VOCs and RFGs. Along with VOC-FTIR and RFG-FTIR, hetero 2D-COS provided novel insights into the synergistic evolution and correlations of gas−solid products during CBF pyrolysis.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…On the other hand, as a result of strong acids and alkalis, the problem of solving the complex compositions of waste water from mid–low‐temperature pyrolysis is extremely difficult. An increase in the scale of pyrolysis production will definitely increase water consumption in a watershed . Therefore, strategies to address the aforementioned factors should be developed.…”
Section: Technology Comparison and Existing Problemsmentioning
confidence: 99%
“…An increase in the scale of pyrolysis production will definitely increase water consumption in aw atershed. [42,[54][55][56] Therefore, strategies to address the aforementionedf actorss hould be developed. Va rious mitigation strategies can be employed to minimize the productiono fw astewater, including the requirement of infrastructure constructions to solve the problems of the pretreatment of ammonia nitrogen, separationo fc oke tar, and phenolr emoval.…”
Section: Difficulty In Addressing Waste Watermentioning
confidence: 99%
“…To improve the hydrogasification reactivity of coal, researchers have performed several research studies. Hong et al (2013) used potassium-and sodium-based catalysts and found a significant effect on the formation of methane under a hydrogen atmosphere. Murakami et al (2000) studied Ni catalytic hydrogasification of coal and found that nickel species had a good catalytic effect on the hydrogasification reactivity of brown coal.…”
Section: Introductionmentioning
confidence: 99%